Methods of fuzzy logic as an instrument for forecasting of tax revenues - Grytskiv, Andriy V.; Masliy, Vadym (Metoda logiki rozmytej jako narzędzie do prognozowania dochodów podatkowych, 2011)
Updating of forecasting for tax revenues is one of the most important directions to increase the efficiency of fiscal bodies’ operations within the budget process. Scientifically substantiated forecasting plays an important role both in the formation of middle-term budget revenues on different levels and is of major influence upon managerial decision-making being under way. The article deals with the comprehensive research of modified approach to forecasting budget revenues volumes based on the usage of obscure time rows (OTR). The authors presented the main terms dealing with obscure time rows, made a digest of the major known methods of OTR forecasting, described the modified approach to forecasting, and analyzed the obtained results.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 9-19
Keywords: dochód podatkowy; logika; prognozowanie; logika rozmyta; tax revenue curve; logic; forecasting; fuzzy logic